2010
DOI: 10.1002/ana.22271
|View full text |Cite
|
Sign up to set email alerts
|

Plasma epidermal growth factor levels predict cognitive decline in Parkinson disease

Abstract: Objective-Most people with Parkinson's disease (PD) eventually develop cognitive impairment (CI). However, neither the timing of onset nor the severity of cognitive symptoms can be accurately predicted. We sought plasma-based biomarkers for CI in PD.Methods-A discovery cohort of 70 PD patients was recruited. Cognitive status was evaluated with the Mattis Dementia Rating Scale-2 (DRS) at baseline and on annual follow-up visits, and baseline plasma levels of 102 proteins were determined with a bead-based immunoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 127 publications
(114 citation statements)
references
References 31 publications
2
110
0
2
Order By: Relevance
“…Confirming previous data, 107 Pellecchia et al 108 showed the association between levels of epidermal growth factor, measured at the time of PD diagnosis and cognitive deficits within 2-year follow-up, with particular regard to executive dysfunctions.…”
Section: Neurotrophic Factorssupporting
confidence: 73%
“…Confirming previous data, 107 Pellecchia et al 108 showed the association between levels of epidermal growth factor, measured at the time of PD diagnosis and cognitive deficits within 2-year follow-up, with particular regard to executive dysfunctions.…”
Section: Neurotrophic Factorssupporting
confidence: 73%
“…In addition, altered expression of the vitamin D receptor (VDR) in blood and reduced plasma levels of 25-hydroxy vitamin D 3 have been associated with PD (1,4). Furthermore, plasma levels of the epidermal growth factor have been associated with cognitive decline in PD (5).…”
mentioning
confidence: 99%
“…The contribution of inflammation to the pathophysiology of PD has been proposed based on epidemiological, genetic and immunological studies in humans and animal models, as well as in postmortem evaluations [4]. Inflammatory and immune mechanisms described in PD can not only exacerbate or hasten the progression of the disease, but also explain, at least in part, some of the clinical symptoms experienced by PD patients [5,6,7,8]. …”
Section: Introductionmentioning
confidence: 99%